Altered anal slow‐wave pressure activity in low anterior resection syndrome: short case series in two independent specialist centres provide new mechanistic insights. (3rd January 2021) - Vollebregt, Paul F.; Wiklendt, Lukasz; Ang, Daphne; Venn, Mary L.; Mekhael, Mira; Christensen, Peter; Dinning, Phil G.; Knowles, Charles H.; Scott, S. Mark
Abstract: Aim: Conventional parameters (anal resting and squeeze pressures) measured with anorectal manometry (ARM) fail to identify anal sphincter dysfunction in many patients with low anterior resection syndrome (LARS). We aimed to assess whether there are differences in anal canal slow‐wave pressure activity in LARS patients and healthy individuals. Method: High‐resolution ARM (HR‐ARM) traces of 21 consecutive male LARS patients referred to the Royal London Hospital, UK ( n  = 12) and Aarhus University Hospital, Denmark ( n  = 9) were compared with HR‐ARM data from 37 healthy men. Results: Qualitatively (by visual inspection of HR‐ARM recordings), the frequency of slow‐wave pressure activity was strikingly different in 11/21 (52.4%) LARS patients from that observed in all the healthy individuals. Quantitative analysis showed that peaks of the mean spectrum in these 11 LARS patients occurred at approximately 6–7 cycles per minute (cpm), without activity at higher frequencies. An equivalent pattern was found in only 2/37 (5.4%) healthy individuals ( P  < 0.0001). Peaks of the mean spectrum in healthy individuals were concentrated at 16 cpm and 3–4 cpm. Conclusion: Over half of the male LARS patients studied had altered anal slow‐wave pressure activity based on analysis of HR‐ARM recordings. Further studies could investigate the relative contributions of sex, human baseline variance and neoadjuvant/surgical therapies on anal slow waves, and correlate the presence of abnormal activity with symptom severity.